Digital KWH meter - Lily Suraiya, Ramely (2009)
The purpose of this project is to develop a digital KWh meter and display the instantaneous values of current (I), voltage (V), and power (P), and total energy (KWh) consumed by load on liquid crystal display (LCD). The scopes include developing hardware to measure instantaneous current, voltage and power consumed by load and also interfacing the hardware with PlC microcontroller so that energy can be calculated. This research was about the alternative for electromechanical induction meter which is widely used to measure energy consumed by load. First, both current and voltage that is used by load will be measured. Then, both values will be fed to ADE7753. The total energy will be calculated and the output will be in form of pulse. Finally the output from the ADE7753 will send to the PlC microcontroller and will be displayed on LCD. Furthermore, users can choose the desired readings to be displayed using the selection buttons.